PENGUATAN PARTISIPASI PEREMPUAN DALAM PEMBANGUNAN DI DESA KARUNIA KECAMATAN PALOLO KABUPATEN SIGI - Daniel T Todapa; Juemi Juemi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The implementation of community service activities was carried out in Karunia Village. The target was residents/community of Karunia Village, Palolo District, especially women. One strategy to realize gender justice and equality is to make gender the mainstream in development. Karunia Village is one of the villages in Palolo District where the level of female participation is still low. The purpose of this community service is to provide reinforcement about the importance of women's participation in development. Women's empowerment is a strategic way to increase women's potential and increase women's roles so that the level of community understanding of the importance of women's roles in development in Karunia Village, Palolo District .